Effect of aging on immunogenicity and efficacy of inactivated influenza vaccines in cotton rats Sigmodon hispidus - Marina S. Boukhvalova; Emma Mortensen; Aissatou Mbaye; Jamall McKay; Jorge C.G. Blanco (Taylor & Francis Group, 2021)
Inactivated influenza vaccines are known to be less immunogenic in human elderly in regards to serologic antibody response induced by vaccination. Accumulating evidence, however, points to a comparable effectiveness of influenza vaccines in the young and the elderly individuals. In the current study, we assessed immunogenicity and effectiveness of trivalent inactivated vaccine FluLaval in young and aged cotton rats Sigmodon hispidus and found that while serologic response to immunization was indeed reduced in older animals, comparable protection against influenza infection was afforded by prime-boost vaccination in both young and aged cotton rats. Both hemagglutination inhibition (HAI) titers and seroconversion rates were lower in the aged animals compared to the young ones. Reduction of viral load in the lung and nose, however, was comparable between young and aged animals vaccinated twice. One-time immunization with FluLaval was less efficacious at protecting the nose of aged animals, indicating that boosting of preexisting immunity can be particularly important for nasal protection in the elderly. Coincidentally, a one-time immunization with FluLaval had a detrimental effect on pulmonary pathology in the young animals, suggesting that boosting of immunity is essential for the young as well. Overall, these results suggest that reduced antibody response to and sufficient efficacy of influenza vaccines in the elderly are not two irreconcilable phenomena and that incomplete immunity to influenza can be detrimental at any age.